Lipopolysaccharides modulate intestinal epithelial permeability and inflammation in a species-specific manner - Stephens, Matthew; von der Weid, Pierre-Yves (Gut microbes, 2020)
Patients presenting with Inflammatory bowel disease have been shown to exhibit an altered microbiome in both Crohn's disease and Ulcerative colitis. This shift in the microbial content led us to question whether several of these microbes are important in inflammatory processes present in these diseases and more specifically whether lipopolysaccharides from the gram-negative cell wall differentially stimulates resident cells. We, therefore, investigated the possible contribution of five major species of gram-negative bacteria found to be altered in presence during disease progression and evaluate their pathogenicity through LPS. We demonstrated that LPS from these different species had individual capacities to induce NF-κB and pro-inflammatory IL-8 production from HEK-TLR4 cells in a TLR4 dependent manner. Additional work using human intestinal colonic epithelial cell monolayers (Caco-2) demonstrated that the cells responded to the serotype specific LPS in a distinct manner, inducing many inflammatory mediators such as TNF-α and IL-10 in significantly altered proportions. Furthermore, the permeability of Caco-2 monolayers, as a test for their ability to alter intestinal permeability, was also differentially altered by the serotype specific LPS modulating trans-epithelial electrical resistance, small molecule movement, and tight junction integrity. Our results suggest that specific species of bacteria may be potentiating the pathogenesis of IBD and chronic inflammatory diseases through their serotype specific LPS responses.